PENGARUH KUALITAS LAYANAN DAN NILAI PELANGGAN TERHADAP LOYALITAS PELANGGAN - Agistia, Ni Made Meta; Nurcaya, I Nyoman (E-Jurnal Manajemen, 2019)
Customer Loyalty is a commitment that is firmly held by the consumer towards a product or service. The purpose of this study is to determine the effect of service quality and customer value on customer loyalty at Ahass Wijaya motor workshop in Denpasar City. This research was conducted in Denpasar city. The number of  samples is 120 samples, by using purposive sampling technique. Data collection method is done through the spreading of questionnaire and the analysis technique used is multiple linear regression analysis. The results showed quality of service and customer value have a positive effect on customer loyalty, so the better the service quality and customer value, the higher the loyalty level of the customer. thus all hypotheses are accepted. Advisable for the company to keep the quality of customer service and value in order to increase customer loyalty.